Pengaruh Model Pembelajaran Kooperatif Student Teams Achievement Division dengan Kemampuan Awal Matematis terhadap Pemahaman Konsep Matematis Siswa - Sumini Sumini; Kns Muhammad Amin Fauzi; Ishaq Nuriadin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the understanding of students' mathematical concepts taught using the Student Teams Achievement Division (STAD) with a problem-based learning (PBM) approach with a heuristic approach; the effect of STAD learning with the PBM approach on students' understanding of mathematical concepts in terms of high and low Initial Mathematical Ability (KAM); the effect of STAD learning with a heuristic approach on students' understanding of mathematical concepts in terms of high and low KAM; the effect of the interaction between STAD learning (with the PBM approach and the heuristic approach) and the initial mathematical ability (high KAM and low KAM) on students' understanding of mathematical concepts. This research was conducted at SDN 112233 Sidorejo, Labuhanbatu Selatan Regency from October to December 2019. A sample of 44 people was taken by random sampling. The instruments for collecting data were the students' mathematical concept understanding test and the KAM test. The data analysis used the one way annova test, simple regression test, and two way annova test. The results of the analysis show that the students' understanding of mathematical concepts taught using STAD with the PBM approach is higher than that of the STAD with a heuristic approach; There is a positive effect of STAD learning with the PBM approach on students' understanding of mathematical concepts in terms of high and low KAM; there is a positive effect of STAD learning with a heuristic approach on students' understanding of mathematical concepts in terms of high and low KAM; There is a significant interaction effect between STAD learning (with the PBM approach and with the heuristic approach) and the initial mathematical ability (high KAM and low KAM) on students' understanding of mathematical concepts.